Macroeconomic Policy Coordination Approach under Currency Board Arrangements in Bulgaria - Златинов, Димитър (Научни трудове, 2020)
The paper presents the logics and empirical results from testing an original approach for assessing the interaction between fiscal and monetary policies in Bulgaria in 2009-2016. Methodologically the approach is based on combinations of the budget balance and the reserve requirement ratio that satisfy pre-defined cross-sectional macroeconomic identities. Applying it we find that the monetary policy in Bulgaria is predominantly oriented to preserve the stability of the currency regime than stimulating real economy, while the government should find the delicate balance between maintaining the public sector stability and promoting economic development.